2019
DOI: 10.1007/s40194-019-00792-3
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution 3D weld toe stress analysis and ACPD method for weld toe fatigue crack initiation

Abstract: Weld toe fatigue crack initiation is highly dependent on the local weld toe stress-concentrating geometry including any inherent flaws. These flaws are responsible for premature fatigue crack initiation (FCI) and must be minimised to maximise the fatigue life of a welded joint. In this work, a data-rich methodology has been developed to capture the true weld toe geometry and resulting local weld toe stress-field and relate this to the FCI life of a steel arc-welded joint. To obtain FCI lives, interrupted fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…10a). Furthermore, it has been pointed out by other researchers that the spray powder coating used to enhance the optical weld geometry measurement could cover the fatigue-critical notches [45]. Therefore, an LCI scan that did not require non-reflective coating for high-resolution measurements was necessary for the analysis of the local weld notch parameters (see Fig.…”
Section: Characterization Of Notch Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…10a). Furthermore, it has been pointed out by other researchers that the spray powder coating used to enhance the optical weld geometry measurement could cover the fatigue-critical notches [45]. Therefore, an LCI scan that did not require non-reflective coating for high-resolution measurements was necessary for the analysis of the local weld notch parameters (see Fig.…”
Section: Characterization Of Notch Geometrymentioning
confidence: 99%
“…Alam et al observed the fluctuating nature of the weld transition radius in scanned laser-hybrid welds and the detrimental effect of the weld ripples at the weld toe [44]. Fatigue crack initiation in arcwelded specimens was shown to take place in areas of high stress concentration factors by Chaudhuri et al,utilizing 3D scans and alternating current potential drop (ACPD) probes at the weld toe [45]. Niederwanger demonstrated a significant improvement in fatigue life prediction utilizing detailed scanned weld geometry (with a scan resolution of 50 µm and accuracy of 25 µm) in FEA compared to idealized weld geometry [46].…”
Section: Introductionmentioning
confidence: 99%
“…The notched specimens were tested with an MTS® servo-hydraulic testing machine at a frequency of 2 Hz until initiation. Initiation is detected by means of the alternating current potential drop (ACPD) technique [40] with a Matelec® CGM-7 device. The principle of this device is to supply the tested specimen with an alternating current and to measure the potential on both sides of the notch.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Kaffenberger and Vormwald [17,18] proposed modelling recommendations for idealized weld geometry simulations, based on the notch stress concept and 3D scanning of overlap and tee joints. Hou [19,20] and Chaudhuri et al [21] modelled the measured 3D weld geometry to predict experimentally observed beachmark locations and crack measurements, respectively, based on weld toe stress concentration factors (SCF). Aldén et al [22] performed detailed 3D simulations on cruciform joints of different weld classes showing that, while the maximum von Mises stress gives a good indication on the fatigue failure initiation location, it gives ambiguous predictions of the fatigue strength.…”
Section: Introductionmentioning
confidence: 99%